2006
DOI: 10.1111/j.1742-1241.2006.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in human in sustained and white coat hypertension

Abstract: Oxidative stress is thought to play a critical role in the pathogenesis of hypertension. Protein oxidation is defined here as the covalent modification of a protein induced either directly by reactive oxygen species or indirectly by reaction with secondary by-products of oxidative stress. The aim of our study was to evaluate the protein oxidation and to examine the function of the antioxidative system in sustained and white coat hypertensives (WCH) and compare with normotensives. This study was designed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
1
18
3
Order By: Relevance
“…158 In patients with white coat hypertension serum protein carbonyl (indicating protein oxidation) was increased and endogenous antioxidant proteins (protein thiol, SOD, glutathione) were decreased compared with normotensive individuals, suggesting a relationship between oxidative stress and hypertension. 159 Antioxidant vitamins reduced blood pressure and arterial stiffness in patients with diabetes or hypertension in small clinical studies, 160 but had no effect in postmenopausal women, in healthy subjects or in pregnant women at risk for hypertension/preeclampsia. [159][160][161][162] …”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…158 In patients with white coat hypertension serum protein carbonyl (indicating protein oxidation) was increased and endogenous antioxidant proteins (protein thiol, SOD, glutathione) were decreased compared with normotensive individuals, suggesting a relationship between oxidative stress and hypertension. 159 Antioxidant vitamins reduced blood pressure and arterial stiffness in patients with diabetes or hypertension in small clinical studies, 160 but had no effect in postmenopausal women, in healthy subjects or in pregnant women at risk for hypertension/preeclampsia. [159][160][161][162] …”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…159 Antioxidant vitamins reduced blood pressure and arterial stiffness in patients with diabetes or hypertension in small clinical studies, 160 but had no effect in postmenopausal women, in healthy subjects or in pregnant women at risk for hypertension/preeclampsia. [159][160][161][162] …”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…Among the oxidative stress parameters, paraoxonase (PON-1) levels were significantly lower (P < 0.001) and malondialdehyde (MDA) levels were higher (P < 0.026) in WCHT patients compared with NT patients, whereas ox-LDL was not significantly different between the NT, WCHT and SHT groups [47] . A study by Caner et al [48] on other oxidative stress parameters, such as protein carbonyl(PCO) and antioxidant capacity, showed that PCO was higher (P < 0.001) and that antioxidant markers(plasma thiol, plasma CuZn-SOD and erythrocyte glutathione) were lower (P < 0.01)in WCHT patients compared with the NT group. Plasminogen activator 1(PAI-1) and von Willebrand factor levels were not different between the WCHT and NT groups [45] .…”
Section: White-coat Hypertension and Target Organ Damagementioning
confidence: 99%
“…Antioxidant vitamins reduced blood pressure and arterial stiffness in patients with diabetes (240), but had no effect in postmenopausal women or in healthy subjects (140). Population studies have demonstrated an inverse association between plasma vitamin C levels and vitamin C consumption with blood pressure (28,139), and a recent meta-analysis reported that vitamin C supplementation reduced systolic and diastolic blood pressure (147). In patients with white coat hypertension, serum protein carbonyl (indicating protein oxidation) was increased and endogenous antioxidant proteins (protein thiol, SOD, glutathione) were decreased compared with normotensive individuals, further supporting a relationship between low antioxidant capacity, increased oxidative stress, and hypertension (201).…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%